SECOND ORDER UPWIND DIFFERENCING SCHEME OF K-ï¥ TURBULENCE MODEL FOR AIR AND EGR FLOW MIXTURES IN INTAKE MANIFOLD OF DIESEL ENGINE - Syaiful, Syaiful; Hendarto, Tommy (ROTASI, 2011)
Fluent is one of the commercial software of computational fluid dynamics using a finite volume of discritization method.This method devides a domain of model becoming several small finite volumes. This software may be used to predict the fluid flow, heat transfer, chemical reaction and other fluids phenomena. In the recent study, the Fluent is used as a tool to predict the characteristics of air and partial exhaust gas mixtures in an intake manifold of diesel engine.In this modeling, the observed mixtures characteristics are the fluid flow and temperature distributions. The type of fluid flowing in the intake manifold of EGR is a turbulent flow. Fluent serves some turbulence models which are k-Îµ, k-Ï‰ and Reynolds Stress Model (RSM) models. Each turbulence model has a different characteristics. It is important, therefore, to know the appropriate turbulence model type for investigating the fluid flow mixtures phenomena in the intake manifold. The fluids flowing into this intake manifold are varied based on the percentage of opening valve EGR, opening load valve and diesel engine speeds. The study shows that the k-Îµ turbulence model is the best model than the other models. This turbulence model has small error with the experimental results for several the opening load valves in which for opening load valve of 0% (0.374% error), 50% (0,495% error), 75% (0,444% error) dan 100% (0,505% error). However, the k-ï· turbulence model has the smallest error (0.381%) at the opening load valve of 25%.